Impactos ambientais decorrentes da ocupação de áreas reguladoras do aporte de areia: a planície Costeira da Caponga, município de Cascavel, litoral leste cearense - Antonio Jeovah de Andrade Meireles (Confins)
Environmental impacts caused by the occupation of areas regulating the sand input to the coast line in the coastal plain of Caponga, Cascavel town, East Coast of Ceará. To determine the environmental impacts related to human occupation in areas characterized by the input of sediments (bypass) to the coastal line, through dunes and estuary, we carried out geoenvironmental studies in the coastal plain of Caponga. They included sections represented by a headland, coastal line and river mouth of the estuarine channel of Caponga. The results were represented in integrated evolutionary models based on the definition of flows of matter and energy that occur in the coastal area. The effects of urban expansion on the headland, dunes, shore and estuarine channel were characterized so as to define adequate measures of planning and management.